Ñemperỹ Jevy : resgatando tradições, inventando patrimônios - Vieira, Driéli da Silva (2012)
The current research was carried out with the Guarani (Nhandéva) from Tekoha Porã in the city of Guaíra, Paraná. The interest in studying this ethnic group originated due to a choir and dance group being formed at that place, as well as the compiling of a book of narratives about the chief of the tekoha?s life. According to the leader, the objective of these measures was to keep this heritage alive for the youth. Then, I started thinking about what the Guarani understood by heritage. Why were dancing, singing and narratives chosen as part of their cultural heritage? What?s the importance of these practices for them? In order to answer these questions, first of all, I searched for bibliographical data by reviewing studies on the Guarani from the colonial period up to the present. Then, I devoted myself to studying about heritage and, at last, through field research aimed to have better understanding of how the Guarani approach dance, singing and narratives